2019
DOI: 10.1016/j.celrep.2019.01.072
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Rhythms Spatially and Temporally Organize Autophagy

Abstract: SUMMARY Circadian rhythms are a hallmark of physiology, but how such daily rhythms organize cellular catabolism is poorly understood. Here, we used proteomics to map daily oscillations in autophagic flux in mouse liver and related these rhythms to proteasome activity. We also explored how systemic inflammation affects the temporal structure of autophagy. Our data identified a globally harmonized rhythm for basal macroautophagy, chaperone-mediated autophagy, and proteasomal activity, which concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 66 publications
3
34
0
Order By: Relevance
“…There is considerable evidence that diurnal/circadian rhythm is associated with the induction of autophagy [44,53], a key regulator of autophagy; the mechanistic target of rapamycin (mTOR) is regulated by the circadian clock [54] and the circadian regulation of metabolism is mediated through reciprocal signaling between the clock and metabolic regulatory networks such as autophagy [44]. Recently, Ryzhikov and colleagues reported that diurnal rhythms spatially and temporarily organize autophagy [55]. They reported that basal autophagy rhythms could be resolved into two antiphase clusters that were distinguished by the subcellular location of targeted proteins.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable evidence that diurnal/circadian rhythm is associated with the induction of autophagy [44,53], a key regulator of autophagy; the mechanistic target of rapamycin (mTOR) is regulated by the circadian clock [54] and the circadian regulation of metabolism is mediated through reciprocal signaling between the clock and metabolic regulatory networks such as autophagy [44]. Recently, Ryzhikov and colleagues reported that diurnal rhythms spatially and temporarily organize autophagy [55]. They reported that basal autophagy rhythms could be resolved into two antiphase clusters that were distinguished by the subcellular location of targeted proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Average intracellular Aβ concentration 〈C S3 〉 (first and third rows) and extracellular Aβ concentration 〈C ES3 〉 (second and fourth rows) at β/β (0) = 10 (upper two rows) and β/β (0) = 100 (lower two rows), depending upon changes of r l3 / r l3 (0) (first column), r h3 /r h3 (0) (second column), and r l3 /r l3 (0) and r h3 /r h3 (0) together (third column). At data points in purple, oscillations of Aβ concentrations are observed; at green data points, concentrations are stationary "autophagy oscillations" are qualitatively similar to those observed in biological experiments [60][61][62][63][64][65][66][67][68][69]. However, mechanisms underlying the phenomena have only begun to be explored [68][69][70].…”
Section: Discussionmentioning
confidence: 57%
“…Nutrient status, oxidative stress, inflammation, the osmotic environment and mechanical loading are the most common factors that induce changes in autophagy and CR in IVDs. Considering the great deal of evidence regarding nutritional status 42,56,60,61,[74][75][76] , we are also particularly interested in this field. As we described above, a periodic lack of nutrition favors the molecular CR, autophagy and their interaction, while a lack of nutritional oscillation, as observed in the context of diabetes, leads to dysfunction of autophagy 60,61,74 .…”
Section: Discussion and Prospectsmentioning
confidence: 99%
“…This was the first evidence of a link between autophagy and circadian regulation, which was established in the early 1970s 47 . Additional evidence of autophagy regulation by CR in the kidney, heart, liver, brain, and retina has been found via electron microscopy, autophagic flux measurements and fluorescence measurements, not only in mammals but also in Drosophila and zebrafish 13,[48][49][50][51][52][53][54][55][56][57][58][59] .…”
Section: The Circadian Rhythm Of Autophagymentioning
confidence: 90%
See 1 more Smart Citation